Telaah Komitmen Organisasi: Pengaruh Atas Penilaian Kinerja, Perencanaan Karier dan Partisipasi Karyawan - Sondari Gadzali, Silvy (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Much empiric research had been conducted on the antecedents of employee organizational commitment. However, there is still less research that examines the effect of HR management praxis, such as performance appraisal systems, career planning systems, and employee participation on organizational commitment. In this study, I tested the impact of these three variables in explaining employee work commitments in the banking sector in West Java. Based on a survey of 98 employees in 20 private banks in West Java, this study uses regression analysis, correlation analysis, and G-test to test hypotheses. The results showed that the performance appraisal system, career planning system and employee participation significantly influence employee work commitment. This result also indicates that the level of organizational commitment of employees in the private banking sector in West Java is low. Therefore, this study suggests that for employees to be genuinely committed to their work, companies must make objective efforts in managing performance appraisals, career planning, and employee participation to ensure effective implementation and to achieve expected results. Keywords: performance appraisal system, career planning, employee participation, organisational commitment